Characterisation of mecA gene negative Staphylococcus aureus isolated from bovine mastitis milk from Northern Germany - Sheet, O H; Grabowski, N T; Klein, G; Reich, F; Abdulmawjood, A (Folia microbiologica, 2019)
Staphylococcus aureus (S. aureus) is an important causative agent of contagious intermammary infections in dairy cattle. S. aureus is also considered as an important foodborne pathogen and cause of food poisoning cases and outbreaks worldwide. In order to understand the molecular ecology of S. aureus, the present study compared phenotypic and genotypic characteristics of 70 S. aureus isolates from bovine mastitis milk samples collected during the period from August 2001 to March 2014 in different regions of Northern Germany. The S. aureus isolates were characterised phenotypically, as well as genotypically for their genetic diversity using multi-locus sequence typing (MLST), spa typing and the presence of virulence genes encoding 16 staphylococcal enterotoxins (sea-selu), toxic shock syndrome toxin (tst), thermonuclease (nuc), clumping factor (clfA and clfB), coagulase (coa) and the methicillin resistance gene mecA. A total of 16 sequence types were grouped into eight clonal complexes (CCs), and 17 spa types were identified. These included six novel sequence types and one novel spa type. The majority of bovine mastitis milk-associated sequence types belonged to the clonal complex CC5, CC97, CC133, and CC151 and showed closely related genotypes or lineages with sequence types of human origin. The genotype CC133 (ST133-t1403) was predominant, constituting 27.1% of the isolates. In addition, the S. aureus isolates displayed nine different enterotoxigenic profiles. All S. aureus were methicillin-susceptible (MSSA). The current study provides new information on phenotypic and genotypic traits of S. aureus isolates from bovine mastitis. The comparison of characteristics of isolates from the present study originating from mastitis milk showed similarities with human isolates. This might help to better understand the distribution of S. aureus in the one health context.
Keywords: Staphylococcal Infections; Staphylococcus aureus; Humans; Virulence Factors; Multilocus Sequence Typing; stafylokokové infekce; Genes, Bacterial; Female; Phenotype; Genotype; lidé; zvířata; Penicillin-Binding Proteins; Germany; bakteriální proteiny; faktory virulence; Food Microbiology; Německo; Mastitis, Bovine; Cattle; ženské pohlaví; Milk; Drug Resistance, Bacterial; fenotyp; multilokusová sekvenční typizace; bakteriální geny; skot; Bacterial Proteins; genotyp; bakteriální léková rezistence; mastitida skotu; Animals; mléko; proteiny vázající penicilin; Enterotoxins; enterotoxiny; potravinářská mikrobiologie